Number 54 (January 2013) (Southeastern Fishes Council Proceedings, 2013)
Reproductive Biology of the Frecklebelly Darter, Percina stictogaster (Teleostei: Percidae) by David J. Eisenhour, Audrey M. Richter, Lynn V. Eisenhour, and Carol-Rose Gingra Post-Hurricane Katrina Survey for the Blackmouth Shiner (Notropis melanostomus) at Historical Localities in Mississippi by Martin T. O’Connell and Ann M. Usee O’Connell Rediscovery of a lost Paratype of the Boulder Darter, Etheostoma wapiti by Michael H. Doosey Minutes, Business Meeting, 37th Annual Meeting, Southeastern Fishes Council 2011 Treasurer's Report for the Southeastern Fishes Council